Opioid use by cancer status and time since diagnosis among older adults enrolled in the Prostate, Lung, Colorectal, and Ovarian screening trial in the United States. (26th February 2021) - Durham, Danielle D.; Strassels, Scott A.; Pinsky, Paul F.
Abstract: Background: Dosing limits in opioid clinical practice guidelines in the United States are likely misapplied to cancer patients, however, opioid use may be difficult to ascertain as they are largely excluded from opioid use studies. Methods: The primary objective was to determine whether cancer patients were more likely to be chronic opioid users after diagnosis. We described prescription opioid use among U.S. older adult cancer patients during two time periods, within 2 years of diagnosis (short‐term) and at least 2 years beyond diagnosis (long‐term), compared to those without cancer (controls). Among participants in the Prostate, Lung, Colorectal, and Ovarian (PLCO) screening trial with linkages to Medicare Part D data during 2011–2015, we used multivariable logistic regression to estimate the association between cancer diagnosis and opioid use outcomes controlling for demographics. The primary outcome of opioid use was measured with the following metrics: Any opioid use, chronic use (90 consecutive days supply of opioid use while allowing for a 7‐day gap between refills), high use (average daily morphine equivalent (MME) ≥120 mg for any 90‐day period), and total MME dose above 2, 000 mg (MME2000 ). Results: The short‐term cohort included 1, 491 cancer patients and 24, 930 controls. Any use in the 2‐year post‐diagnosis period was higher among cancer patients OR 3.3 (95% CI: 3.0–3.7). Chronic use rates were similar by cancer status (4.6% vs. 3.8% for cases and controls, respectively). The long‐term cohort included 4, 377 cancer patients and 27, 545 controls. Rates of any use were similar among cancer patients and controls (63% vs. 59%). Conclusions: Any opioid use was similar among long‐term cancer survivors compared to controls, but differed among short‐term survivors for any opioid use and marginally for chronic opioid use. Abstract : Use of any opioid was similar among long‐term cancer survivors compared to controls, but differed among short‐term survivors for any opioid use and marginally for chronic opioid use. Continued monitoring of opioid use among subgroups of cancer patients is important. This should include concomitant use of opioids and non‐opioid medications commonly used to manage pain among cancer patients.